Assessment Strategies to Evaluate Building Information Modeling Capabilities of Organizations. Issue 1 (February 2021) - Khohar, H A; Rahman, R A; Haron, A T; Esa, M
Abstract: With the advances in technology, Building Information Modeling (BIM) has been implemented in construction projects to minimize its complexity by increasing project efficiency and effectiveness. While BIM has been widely implemented, construction projects are still unsuccessful due to inappropriate BIM capabilities among organizations that are involved in the project. Therefore, this study aims to determine the strategies for assessing an organization's BIM capabilities. The data collected through individual interviews with fifteen of BIM managers are analyzed using thematic analysis in order to achieve that objective. The findings suggest that the five parameters for evaluating an organization's BIM capabilities are: documentation process, project track record, staff competencies, availability of BIM experts, and software maturity. This study contributes by providing a set of strategies for measuring an organization's BIM capabilities in the construction industry. The lesson of this study would help researchers and industry practitioners prevent construction project failure from assessing project team members' BIM capabilities before starting a project.